Sensitive experience and political positioning in “Object and Participation” - Ribeiro, Roney Jesus (Revista do Colóquio, 2025)
This article aims to analyze the exhibition “Object and Participation” (1970), held at the Palácio das Artes in Belo Horizonte, highlighting its experimental and politically engaged character. The research adopts a qualitative methodology, of an analytical and exploratory nature, examining the artistic propositions in dialogue with the socio-political reality of Brazil in the 1970s, a period marked by the military dictatorship. Organized by Frederico Morais, the exhibition valued the active participation of the public through innovative visual languages ​​and sensory experiences. The artistic propositions presented in the exhibition in question constituted critical and collective interventions, capable of questioning the traditional art system and provoking reflection on the injustices and social conflicts of the period, consolidating the exhibition as a landmark of guerrilla art or “counter-art” in Brazil.